ผลการประเมินโปรแกรมเพิ่มพูนประสบการณ์การแก้ปัญหาสำหรับนักเรียนที่มีความสามารถพิเศษทางภาษาระดับประถมศึกษา - ศักดิ์วีระกุล, ธิดารัตน์; ศรีวันยงค์, ศิริพันธ์; อนุรุทธ์วงศ์, อุษณีย์ (Journal of Research and Curriculum Development, 2016)
บทคัดย่อไม่สมบูรณ์ An Evaluation of an Enrichment Program for Enhancing Problem Solving Skills in Linguistically Gifted Primary School Students This research aimed at evaluating the appropriateness of an enrichment program for enhancing problem solving skills in linguistically gifted primary school students by using Kirkpatrick's Program Evaluation Method and Eisner's Educational Connoisseurship and Criticism Model and Criticism Model. The research revealed that the program was appropriate for organizing activities to promote problem solving skills in linguistically gifted primary school students, with a face validity between .85-1.00.